Potential of Distilled Liquid Smoke Derived from Coconut (Cocos nucifera L) Shell for Traumatic Ulcer Healing in Diabetic Rats - Surboyo, Meircurius Dwi Condro; Arundina, Ira; Rahayu, Retno Pudji; Mansur, Dieni; Bramantoro, Taufan (European Journal of Dentistry, 2019)
Objective Distilled liquid smoke (DLS) is a result of coconut processing by-product that not only serves as a natural food preservative but also has a promising therapeutic effect. The healing potential of DLS derived from coconut (Cocos nucifera L) shell was investigated on a traumatic ulcer with the diabetic rat.Materials and Methods DLS was analyzed the component by gas chromatograph mass spectrometry. Diabetic condition was induced by alloxan in 55 male Wistar rats. Ten mm of traumatic ulcer was made along the labial fornix incisive inferior after the diabetic condition was confirmed. Then DLS coconut shell, benzydamine hydrochloride, and sterile distilled water were applied topically for 3, 5, and 7 days. The potential healing was evaluated based on the expression of nuclear factor kappa beta (NFκB) and tumor necrosis factor alpha (TNF-α) on macrophages using immunohistochemical staining and the amount of collagen using Masson Trichome staining. The difference between each group was analyzed using one-way analysis of variance. The least significant difference test is used to determine the significant difference (p < 0.05).Results The major compounds found were phenol (36.6%), 2-methoxyphenol (guaiacol) (25.2%), furfural (17.8%), and 4-ethyl-2-methoxyphenol (3.5%) with 28 other minor constituents. The lowest NFκB and TNF-α expression on macrophage was observed by topical application of DLS derived from coconut shell for 3, 5, and 7 days of treatment. The amount of collagen was increased and indicated by the highest result of DLS compared to others.Conclusion The DLS derived from coconut (Cocos nucifera L) shell was able to improve traumatic ulcer healing in a person with diabetes.
Keywords: coconut shell; diabetic; distilled liquid smoke; traumatic ulcer healing